Palladium complexes of o-xylyl-linked alkoxybenzimidazolin-2-ylidenes: interesting structural conformations and application as pre-catalysts - Baker, M.; Brown, David; Simpson, P.; Skelton, B.; White, A. (The Royal Society of Chemistry, 2009)
New PdBr2-bis(N-heterocyclic carbene) complexes derived from 4,7-dibutoxybenzimidazole and 5,6-dibutoxybenzimidazole have been synthesized and structurally and spectroscopically characterized.The complexes show much greater solubility compared to the parent complex derived from benzimidazole, and interesting structural characteristics dependent on the position of the butoxy substituents. The complexes display high activities in the coupling of aryl iodides in the Mizoroki-Heckreaction and moderate activities in the Suzuki-Miyaura coupling of inactivated aryl bromides at low catalyst loadings, although activity differences between pre-catalysts has been observed. Structuralstudies suggest electronic effects within the complexes to be strongly affected by steric interactions between the hydrogen atoms of the o-xylyl bridges and the benzimidazole components and their substituents.